Europäische Referenznetzwerke - Graessner, Holm; Schaefer, Franz; Wagner, Thomas O. F. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2017)
Starting in 2017, European Reference Networks (ERNs) for rare disease patients will be established in the European Union. ERNs will pool expertise in clinical centres and will establish cross-border exchange mechanisms in order to facilitate access to diagnosis and care. The integration of ERNs in the German healthcare system will pose a significant challenge. The main issues include: (i) competition between national and European interests in the conflict of national responsibility and intended cross-border availability of healthcare services, (ii) the lack of a funding concept, and (iii) the establishment of ERNs in EU member states in which implementation of national action plans for people with rare diseases is lagging behind. The lower implementation pace of the centre model that is part of the German action plan and the higher level of detail of the ERNs in terms of services and activities provided will likely lead to an appreciation that achieved patient benefits are attributed to ERNs.
Gesehen am 23.04.2018